Fatigue Behavior of Coated and Uncoated.Cemented Carbide Inserts Inverstigated by Impact test at the Cutting Edge Vicinity - Bouzakis, K.-D.; Batsiolas, M.; Skordaris, G.; Michailidis, N.; Stergioudi, F. (International Conference on Plasma Surface Engineering, 2013)
Significant tool life improvements are attained by the application of harder and more wear-resistant materials and coating systems. In this context, the tools’ cutting edges affect directly the overall tool performance. In this paper, by impact tests at the cutting edge vicinity, a quick assessment of the cutting edge fatigue behavior of coated and uncoated cemented carbide inserts is enabled. Various substrate grades were examined and the effect of their surface treatment and coating on the fatigue endurance load was experimentally examined. The FEM simulation of the test procedure at various distances from the inserts’ cutting edge provides an insight in the developed stress fields and enables the fatigue endurance stress determination of the coating-insert system. The contribution of the substrate surface treatment and coating to the endurance of the cutting edge region was revealed. The developed method facilitates a rapid quality control of both coated and uncoated cutting inserts at loading conditions, close to those encountered during their standard operation.